The Language Learning Principles Reflected In EF's English Threshold 2 Textbook - Arianto, Yopi; , Prof. Dr. Endang Fauziati, M. Hum; , Dra. Siti Zuhriah Ariatmi, M.Hum (2013)
The thesis describes the language learning principles in The EF's English Threshold 2, an English textbook published by English First (EF). By doing the research, the researcher could find the language learning principles reflected in English threshold 2, the frequency of them so that the dominant principle could be found, and the implication of language teaching. Subjects of the research are all the instructions and tasks in English Threshold 2. The data gathering was conducted by documentation. The collected data analyzed were qualitative. The findings of the research shows the dominant language learning principle is the cognitivism, while the other three principles comes as follows: the second dominant is behaviorism, the third dominant is constructivism, and the least dominant is humanism. The language learning principles are the perspectives of describing the book so the teacher can hold the findings as the hand-grip in choosing a proper English textbook for their students. And the material developer can use the principles as other consideration of arranging the new English textbook